Sufism in the contemporary art of Malaysia / Ahmadrashidi Hasan and Mizan Hitam - Hasan, Ahmadrashidi; Hitam, Mizan (2012)
This paper disclosed some artists who observed to express Sufism, both ideological and experiential. It discussed the content analysis of their artworks on aspects like image, subject and their meaning from the perspectives of Sufism and also the formalistic aspects which involved the style and visuals. Artists appeared to used the implicit manifestation of expression which involved metaphorical and abstract representation. It is established that there are artists in Malaysia who expressed the ideology of Sufism or expressed the beauty of the spiritual experience of the Sufism.